JEWELRY LEXIS AS THE ETHNIC AND CULTURAL SOURCE (ON THE TATAR LANGUAGE MATERIAL) - Fazlieva, Ilsina I.; Yusupova, Alfiya Sh.; Nurmukhametova, Raushaniya S.; Alkaya, Ercan (Magnanimitas, 2018)
The lexical system of each language contain the elements in which traditions, the people's occupation, way of life, psyche are reflected. Many lexical units store centuries-old history and culture of the people. The present paper deals with description of some lexical units of material culture, the names of ornamentals of the Tatar people. For the purpose of studying these lexemes, descriptive method and continuous sampling method of were used to collect and systematize the materials; lexico-semantic method was introduced when analyzing factual material; methods of linguoculturological, component and semantic analysis were used to highlight the cognitive features of the functioning of linguistic units; comparative and contrastive methods were used when considering the translations in bilingual dictionaries. Review and analysis of factual material confirm that the vocabulary reflects the features of the material economy and the attitude of the people to their ethno-cultural values. In the course of the study, the etymology of the selected units, their relation to the common Turkic heritage, and at the same time, the uniqueness of these items were singled out. The material will further serve as a model and source for studying other layers of the Tatar language vocabulary and for creating an integral image of the material culture of the Turkic peoples.
Keywords: the Tatar language; vocabulary; material culture; the names of jewelry; traditions